The Caribbean: Improving extension through a systems approach; the Caribbean Agricultural Extension Project - Seepersad, J. (1993)
This article outlines a regional programme--the Caribbean Agricultural Extension Project--designed to improve the economic and social well-being of small-farm households, in which The University of the West Indies (UWI) collaborated with USAID
Keywords: Caribbean Agricultural Extension Project